Does Empowering Victim to Earn a Living Reduces the Risk of Domestic Violence Severity? A Narrative Review and A Pilot Study - Chew, Keng Sheng; Shirly Wong, Siew Ling; Siew, Ke Lin; Vanitha, Kandasamy (UNIMAS Publisher, 2023)
Defined as the act of causing or attempting to cause physical, psychological or sexual harm to a person by another person who is either a spouse, former spouse, adult child, parent or any other family members, domestic violence is a global public health issue including in Malaysia. One way to mitigate the risk of domestic violence is through the ability of a domestic violence victim to earn her own income. Unfortunately, although some studies have shown that the higher the income level of the victim, the lesser the risk of domestic violence severity; other studies did not demonstrate this relationship. Using the Transtheoretical Model of Change and Walker’s cycle of abuse, this paper first highlights the importance of creating awareness that domestic violence is not acceptable as well as advocating for a non-judgmental attitude to minimize stigmatization, secondary traumatization and rendering social support in helping victims toward a journey of sustained change. This paper then reports and discusses the results of a self-administered questionnaire pilot study conducted on female domestic violence victims admitted to the Sarawak General Hospital on the impact of income on domestic violence severity. Broadly speaking, the results suggest that the impact of earning income is not as straightforward as it appears to be and hence, not only that it may not reduce the domestic violence severity but paradoxically, may increase its severity.